Combination of violet light irradiation and collagenase treatments in a rabbit model of keratoconus - Kobashi, Hidenaga; Yano, Takashi; Tsubota, Kazuo (Frontiers in Medicine, 2023)
Purpose: We evaluated the use of collagenase treatment to generate a rabbit model of keratoconus and the impact of violet light (VL) irradiation on the disease model in six Japanese White rabbits. Methods: After epithelial debridement, the collagenase group was treated with a collagenase type II solution for 30 min; the control group was treated with a solution without collagenase. Three rabbits also underwent VL irradiation (375 nm, irradiance 310 μW/cm2) for 3 hours daily for 7 days after topical collagenase application. Slit-lamp microscopy results, steep keratometry (Ks), corneal astigmatism, central corneal thickness, and axial length were examined before and after the procedure. The corneas were obtained on day 7 for biomechanical evaluation. Results: A significant increase in Ks and corneal astigmatism was observed in the collagenase and VL irradiation groups compared with the control group at day 7. No significant difference was found in the change in corneal thickness between the groups. The elastic modulus at 10% strain, but not at 3% and 5% strain, was significantly lower in the collagenase group than in the control group. There was no significant difference in the elastic modulus at each level of strain between the collagenase and VL irradiation groups. The average axial length at day 7 was significantly longer in the collagenase group than in the control group. Collagenase treatment induced a keratoconic model by steepening the keratometric and astigmatic values. There was no significant difference in the observed elastic behaviour of normal and ectatic corneas under physiologically relevant stress levels. Conclusion: VL irradiation did not cause regression of corneal steepening in collagenase-induced model during short-term observation.